Madrasah Education Teacher Strategies to Raise Students’ Spiritual Intelligence at Madrasah Aliyah Darul Ulum Al-Muhajirin Langkat - Ruslan Efendi; Ethan Tan; Ava Lee (International Journal of Educatio Elementaria and Psychologia, 2024)
This research describes the strategies of madrasah education teachers to awaken students’ spiritual intelligence at the Aliyah Darul Ulum Al-Muhajirin Langkat madrasah. The aim of this research is to provide education and information to readers that spiritual intelligence can be obtained if students are educated at madrasah educational institutions. This research method is a field method (qualitative), namely the author comes into direct contact with students and teachers to dig up information related to this research. The approach used is an anthropological and sociological approach. Data collection techniques are through observation and unstructured interviews with sources who are considered to have competence, after which the data is obtained and then the data is analyzed scientifically. The location of this research is at Madrasah Aliyah Darul Ulum Al-Muhajirin Langkat. The research results found: First, students are educated with the knowledge of aqidah and muamalah, second, making norms or rules based on Islamic legal principles in the madrasah environment so that students become educated, third, developing spiritual intelligence through Islamic religious education subjects in students who are carried out using the teacher’s approach as a role model for students.